Group planning, creating, and testing : programming together - Miller, Derek L. (Everyday coding., 2018)
Offers a broad explanation of coding in groups, and includes examples of group programming in everyday life. Also discusses debugging programs. Features color photographs, a glossary, resources for information, and an index.